2021
DOI: 10.3390/jcm10194531
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Perioperative Hemodynamic Instability in Pheochromocytoma: A Systematic Review and Meta-Analysis

Abstract: Objective: To evaluate the risk factors of perioperative hemodynamic instability in pheochromocytoma, we conducted a systematic search of the literature using the Preferred Reporting Items for Systematic Reviews and Meta-analysis. Methods: In April 2021, we systematically searched PubMed, the Cochrane library, and Scopus for relevant studies on the risk factors of perioperative hemodynamic instability of adrenalectomy in patients with pheochromocytoma, and we subjected the findings from those studies to formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
14
1
1
Order By: Relevance
“…In addition, another remaining problem is that the definition of an episode of intraoperative hemodynamic instability is not consensual in the available literature ( Table 2 ). In a recent systematic review investigating risks factors for perioperative hemodynamic instability in pheochromocytoma regrouping 14 studies involving 1725 patients, there were 14 different definitions for intraoperative hemodynamic instability [ 46 ]. This demonstrates the lack of uniformity in the scientific community and the strain of comparing studies using different definitions for intraoperative hemodynamic instability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, another remaining problem is that the definition of an episode of intraoperative hemodynamic instability is not consensual in the available literature ( Table 2 ). In a recent systematic review investigating risks factors for perioperative hemodynamic instability in pheochromocytoma regrouping 14 studies involving 1725 patients, there were 14 different definitions for intraoperative hemodynamic instability [ 46 ]. This demonstrates the lack of uniformity in the scientific community and the strain of comparing studies using different definitions for intraoperative hemodynamic instability.…”
Section: Resultsmentioning
confidence: 99%
“…In a systematic study, tumor size and levels of urinary norepinephrine were associated with perioperative hemodynamic instability [ 46 ]. However, the use of alpha-blocking agents for preparation was not associated with intraoperative hemodynamic instability [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other risk factors for HI were reported in the literature, including plasma or urinary level of catecholamine, BMI, clinical symptoms and et al [ 3 , 9 , 23 , 24 ]. Possible reasons for this variability might be a lack of standardized perioperative anaesthesiological and surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study including 61 patients who had undergone pheochromocytoma resection concluded that intraoperative hypertension episodes were similar in MEN2A patients to those in nonsyndromic pheochromocytoma patients, with postoperative hypotension less frequent and severe ( 15 ). However, for MEN2A patients undergoing pheochromocytoma resection, preoperative medications, including phenoxybenzamine or other selective a1-adrenergic blockers, are necessary, and intraoperative hemodynamic instability can be predicted according to their clinical manifestations, laboratory examination and tumor size ( 11 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%